2000
DOI: 10.1128/aem.66.3.1020-1025.2000
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Species from Nepalese Rice and Production of Mycotoxins and Gibberellic Acid by Selected Species

Abstract: Infection of cereal grains with Fusarium species can cause contamination with mycotoxins that affect human and animal health. To determine the potential for mycotoxin contamination, we isolated Fusarium species from samples of rice seeds that were collected in 1997 on farms in the foothills of the Nepal Himalaya. The predominant Fusarium species in surface-disinfested seeds with husks were species of the Gibberella fujikuroi complex, including G. fujikuroi mating population A (anamorph, Fusarium verticillioide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(157 citation statements)
references
References 29 publications
6
143
2
6
Order By: Relevance
“…verticillioides can be an endophyte in maize, the production of fumonisin depends not only on the presence of the fungus, but also on the correct environmental conditions for the strains present to be able to make the toxin. Fumonisin non-producing strains from field samples are known (Desjardins et al 2000), but in general the proportion of these strains to the total population is relatively small. Other explanation for samples with the fungus but no toxin may be because the fungus appeared late and did not have time to produce the toxin or that it was misidentified.…”
Section: Discussionmentioning
confidence: 99%
“…verticillioides can be an endophyte in maize, the production of fumonisin depends not only on the presence of the fungus, but also on the correct environmental conditions for the strains present to be able to make the toxin. Fumonisin non-producing strains from field samples are known (Desjardins et al 2000), but in general the proportion of these strains to the total population is relatively small. Other explanation for samples with the fungus but no toxin may be because the fungus appeared late and did not have time to produce the toxin or that it was misidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium infection and fumonisin contamination is a major problem in Pakistan and 20% of the seeds were found naturally infected by F. verticillioides (4). Desjardins et al (2000) have reported 2980μg/g of fumonisin production from rice culture. This indicates that, even 20% of F. verticillioides infection can be a serious problem, as paddy is the staple food for people of Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In Asia, the incidence of Fusarium and fumonisin contamination is highly prevalent. F. verticillioides contamination has been reported from Nepal, where both local and improved varieties of paddy are affected by F. verticillioides (8).…”
Section: Resultsmentioning
confidence: 99%
“…Bakanae or foot rot disease of rice has been recorded in almost all rice growing countries, especially in Asian countries (Desjardins et al, 2000). Bakanae disease was widespread in Peninsular Malaysia and three provinces of Indonesia with the range of disease severity from scale 1-5 and disease incidence from 0.5-12.5% during 2004-2005 main growing seasons (Zainudin et al, 2008) but the disease may be responsible for yield losses of up to 50% in Asia in outbreak cases.…”
Section: Introductionmentioning
confidence: 99%
“…J., 14 (4): 207-211, 2015 stimulating substances known as gibberellins, which are responsible for excessive elongation of the plants (Malonek et al, 2005). Besides gibberellins, the fungus also produces a phytotoxin, fusaric acid, a non-specific substance which is toxic to the plants (Desjardins et al, 2000). The name "Bakanae" comes from a Japanese word, meaning abnormal elongation of the plants.…”
Section: Introductionmentioning
confidence: 99%